2023
DOI: 10.1021/acs.jpcb.2c08962
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Mechanism of Tunable Thermal Conductivity in Carbon Nanotube-Geopolymer Nanocomposites

Abstract: Geopolymer has been considered as a green and low-carbon material with great potential application due to its simple synthesis process, environmental protection, excellent mechanical properties, good chemical resistance, and durability. In this work, the molecular dynamics simulation is employed to investigate the effect of the size, content, and distribution of carbon nanotubes on the thermal conductivity of geopolymer nanocomposites, and the microscopic mechanism is analyzed by the phonon density of states, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…After ten cycles, the thermal conductivity deviation of the VCF/G-6 composite was only 1.5% (25 °C) and 1.7% (100 °C), confirming the reliability and stability of heat transfer during long-term use. Figure j shows a comparison of the thermal conductivity of our work with other composites that used carbon-based fillers in previous works. ,, …”
Section: Resultsmentioning
confidence: 94%
“…After ten cycles, the thermal conductivity deviation of the VCF/G-6 composite was only 1.5% (25 °C) and 1.7% (100 °C), confirming the reliability and stability of heat transfer during long-term use. Figure j shows a comparison of the thermal conductivity of our work with other composites that used carbon-based fillers in previous works. ,, …”
Section: Resultsmentioning
confidence: 94%
“…It is worth pointing out that we restricted our study to a sodium-based geopolymer with a Na/Al ratio of 1 to ensure the system charge balance. According to our previous research work, we found that the geopolymer system had no obvious size effect, which means that we do not need to consider the impact of the system size on the calculation results. Therefore, we set the size of simulation systems to 80 Å × 40 Å × 40 Å uniformly.…”
Section: Computational Detailsmentioning
confidence: 98%
“…In MD simulations, the interatomic potential is crucial to accurately describe the atomistic interactions. In this work, we chose the interatomic potential that was verified earlier for geopolymer systems with a similar composition, including zeolites, metakaolin, and geopolymers. , In order to facilitate the distinction, we mark the oxygen atom in the geopolymer structure as O s , the oxygen atom in the water molecule as O w , and the hydrogen atom in the water molecule as H w . The expression for the interaction potential of M–O s (M = Si, Al, Na, O s ) is V ( r ) = C q i q j ϵ r + A 0.25em exp ( r ρ ) C r 6 + D r 12 r < r c where the first term is the long-range Coulomb interaction in which C is the energy conversion constant, q i and q j are the charges of atoms i and j , respectively, ϵ is the dielectric constant, which has the default value of 1.0, r is the distance between the two atoms, r c is the cutoff radius set as 12 Å.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation